Analysis of Minimal Marking Technique on Student’s Writing Given by Teachers at MAN Kota Baru, Padang Panjang - Yuniko, Fajrilhuda; Azhari, Andry (PT. Riset Press International, 2024)
This research was based on a phenomenon that the students’ writing ability was still low. It was assumed that there were two main factors influencing the students’ writing. One of them was about facilitating the students with appropriate written feedbacks. In line with that, this research was a kind of descriptive study, which was aimed at finding a deep description of the implementation of minimal marking technique given by teachers at MAN Koto Baru Padang Panjang. Participants of the research were all English teachers there. Furthermore, the data were collected by using two instruments, documents and interview. There were two findings of the research. First, almost all of the written feedback items given through the minimal marking technique were provided to help students working on their grammatical mistakes or forms of the writing, it was proven by the percentage that 99.66% of the written feedback items were focused on forms whereas only 0.34% of the written feedback items were focused on contents. Second, the written feedback technique applied by the English teachers was minimal marking technique. It is used since it is effective for teachers, particularly, in the process of giving the feedback which is time-saving. In addition, it also helps the students to be a critical writer because this technique lets the students working on the mistakes they have made.